Forensic Medicine And Female Victimhood In Victorian And Edwardian England. Issue 1 (4th August 2019) - Bates, Victoria
Abstract: Mistrust of women has been an enduring feature of trials for sexual offences, both historically and in the present day, but is not a transhistorical phenomenon. This article explores the late-Victorian and Edwardian courts, in which there was a renewed tendency to question female respectability and to judge complainants for failing adequately to resist a man's sexual advances. Scholars have identified broad social trends that led to greater interrogation of female sexual behaviour during this period, but there remains limited understanding of the mechanisms by which these concerns entered the courtroom. This article focuses on the rise of a medico-legal framework for investigating sexual violence as one such mechanism. Drawing upon newspaper reports and court cases from Middlesex, Somerset, Gloucestershire and Devon in the period 1850–1914, it shows that medical witnesses often implicitly reinforced social models of 'real' victimhood — which excluded many complainants — through their testimony on female chastity and resistance. Forensic medicine operated as an important, and increasingly unique, bridge between English social change and local courts.